2020
DOI: 10.1021/acs.biomac.0c01059
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Series of New Epoxidized Vegetable Oil-Based Thermosets with Chemical Recycling Properties

Abstract: This work reports for the first time the copolymerization studies of 11 newly synthesized epoxidized vegetable oils (EVOs) that reacted with a disulfide-based aromatic dicarboxylic acid (DCA) to produce thermoset materials with recyclability properties. These new EVOs' reactivity and properties were compared with those of the two commercial references: epoxidized linseed oil (ELO) and epoxidized soybean oil (ESO). The structure−reactivity correlation is proposed by differential scanning calorimetry (DSC) analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
90
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(104 citation statements)
references
References 53 publications
6
90
1
1
Order By: Relevance
“…The hypothesis of the authors is corrected if we consider that it is well known from the literature that the presence of S−S bonds thermally destabilizes thermosets because their lower dissociation energy compared with that of C−C bonds [36]. In addition, the French researchers correctly considered the effect of the oxirane ring content, that lead to the formation of more ester and hydroxyl groups during the curing, thus contributing to the thermal scissions of the networks [37]. Since they found a strictly link among EVO functionality, reactivity, cross-linking density, and final performances, they continued their studies by proposing the synthesis and thermal characterization of a reprocessable thermosets, whose recyclability was designed through a dual mechanism (i.e., disulfide metathesis; transesterifications), obtaining similar performance compared to the control ones.…”
Section: Thermal Techniques In Polymers' Recycling and Preparation Of Recyclable Polymersmentioning
confidence: 99%
“…The hypothesis of the authors is corrected if we consider that it is well known from the literature that the presence of S−S bonds thermally destabilizes thermosets because their lower dissociation energy compared with that of C−C bonds [36]. In addition, the French researchers correctly considered the effect of the oxirane ring content, that lead to the formation of more ester and hydroxyl groups during the curing, thus contributing to the thermal scissions of the networks [37]. Since they found a strictly link among EVO functionality, reactivity, cross-linking density, and final performances, they continued their studies by proposing the synthesis and thermal characterization of a reprocessable thermosets, whose recyclability was designed through a dual mechanism (i.e., disulfide metathesis; transesterifications), obtaining similar performance compared to the control ones.…”
Section: Thermal Techniques In Polymers' Recycling and Preparation Of Recyclable Polymersmentioning
confidence: 99%
“…The development of vitrimers containing dynamic covalent bonds (DCBs) makes it possible to recycle thermosets under mild conditions [8,9,[15][16][17][18][19][20][21][22][23][24][25]. Over the past few decades, researchers have developed an array of vitrimers through incorporating various DCBs (e.g., disulfide [25,26], imine-amine exchange [27], and hindered urea bond [28]), among which epoxy vitrimer prepared from the curing reactions of epoxy-anhydride [29][30][31] or epoxycarboxylic [32][33][34] is the most investigated vitrimer system.…”
Section: Introductionmentioning
confidence: 99%
“…The epoxy resins based on disulfide bonds can be recycled in DMF solution of dithiothreitol [ 14 , 28 , 30 ]. Figure 8 A and Figure S8A present the full degradation and chemical recycling ability after 24 h at 50 °C of the thermosets based on ECMO/DTBA x DTDA y and ECMO/DTBA x 4-AFD y .…”
Section: Resultsmentioning
confidence: 99%
“…Rekondo et al [ 8 ] synthesized a polyurethane elastomer using an aromatic diamine disulfide crosslinker, 4-aminophenyl disulfide (4-AFD), and showed that self-healing occurred at room temperature with a repairing efficiency of more than 95%. Zeng et al [ 9 ] obtained a reprocessable castor oil-based polyurethane by incorporating 4-AFD and reported [ 10 , 11 , 12 , 13 , 14 ] that the mechanical properties were completely recovered after reprocessing. For the first time, our team produced reprocessable, repairable and recyclable epoxidized vegetable oil (EVO) thermosets by using 2,2′-dithiodibenzoic acid (DTBA) as a crosslinker.…”
Section: Introductionmentioning
confidence: 99%